HOLOCENE PALEOCLIMATE ANALYSIS BASED ON SEDIMENT CHARACTERISTICS AND PLANKTONIC FORAMINIFERA ON SUMBA STRAIT, EAST NUSA TENGGARA - Damanik, Adrianus
Holocene Paleoclimate analysis was conducted on Sumba Strait, East Nusa Tenggara. Geographically, this location is located at coordinates 09°04'544" S 119°42'727" E with sample code ST-13. The sample is data of Widya Nusantara Expedition LIPI 2016 taken using gravity core from abouve research ship Baruna Jaya VIII at depth 793 m below sea level with 173 cm length. Sample were sampled at intervals of one cm for grains size and XRF analysis, and eight cm for planktonic foraminifera analysis. Proxies of paleoclimate analysis that used in this research are grain size, element content, and abundance of planktonic foraminifera. Grain size analysis was conducted using Malvern Mastersizer 2000 to obtain grain size parameters such as mean, median, sorting, skewness, kurtosis, and percentiles. XRF analysis was conducted using Thermo Scientific to obtain element content of sample. Analysis of abundance of planktonic foraminifera was conducted using microscope and calculation of abundance of each species in samples. Grain size analysis results show dominance of coarse silt and very coarse silt sediment, and divided into 13 facies. XRF analysis results show that in the sample there are elements of Zirconium (Zr), Strontium (Sr), Rubidium (Rb), Iron (Fe), Manganese (Mn), Titanium (Ti), Scandium (Sc), Calcium (Ca) and Potassium (K), and divided into 7 trends. Foraminifera analysis results show the dominant species are Globigerina spp., Globigerinoides ruber, Globigerinoides trilobus, Hastigerina aequilateralis, Neogloboquadrina accostaensis, Neogloboquadrina dutertei, Neogloboquadrina spp., and Pulleniatina finalis, and divided into 8 trends. Age limit between the Late Plistocene and the Holocene at 167 cm depth marked by the First Appereance Datum (FAD) Bolliela adamsi species. The integration of grain size analysis, XRF, and abundance of planktonic foraminifera show accordance results. Increase of temperature will be showed by increasing of abundance of planktonic foraminifera, particularly in warm temperatures such as Globigerinoides ruber and Globigerinoides trilobus, increasing of grain size, and increasing of Ca and Sc content, and Fe, Mn, and Ti degradation. Based on the integration of the three proxies, the Sumba Strait Paleoclimate condition is divided into six climate changes during the Holocene.